EFFECTIVENESS OF SMOKING CESSATION INTERVENTIONS FOR ADOLESCENTS: A SYSTEMATIC REVIEW - Sutantri, Sutantri (IJNP (Indonesian Journal of Nursing Practices), 2015)
Objective: To present a review of the identified literature related to smoking cessation interventions for adolescents and to summarise the findings and research gaps in this field.Methods: A standard literature search was performed using fourÂ  electronic databases (MEDLINE,Â  CINAHL, PsycINFO, and the COCHRANE LIBRARY) for identification of peer-reviewed articles. Search terms used included â€œsmok* OR tobacco OR cigarette*â€ AND â€quit* OR cessation OR treatmentâ€ AND â€œadolescen* OR teen* OR young people OR youth OR student*â€. The internet and organisational databases were also used to find other types of documents (eg, books and reports). The reference lists of identified relevant documents were reviewed to find additional sources.Results: There are a total of nine studies met the inclusion criteria and exclusion criteria included in this study. In exploring studies related to smoking cessation intervention in this review, researchers divided the studies into two approaches based on the types of intervention; these are psychosocial intervention and pharmacotherapy.Conclusions: This literature review demonstrated that smoking cessation interventions using psychosocial interventions have been promising. From several studies, it can be seen that smoking cessation using this approach has indicated positive results.Keywords: smoking cessation, adolescent, tobacco